Highly Luminescent, Water‐Soluble Lanthanide Fluorobenzoates: Syntheses, Structures and Photophysics, Part I: Lanthanide Pentafluorobenzoates. Issue 49 (22nd October 2015) - Kalyakina, Alena S.; Utochnikova, Valentina V.; Bushmarinov, Ivan S.; Ananyev, Ivan V.; Eremenko, Igor L.; Volz, Daniel; Rönicke, Franziska; Schepers, Ute; Van Deun, Rik; Trigub, Alexander L.; Zubavichus, Yan V.; Kuzmina, Natalia P.; et al.
Abstract: Highly luminescent, photostable, and soluble lanthanide pentafluorobenzoates have been synthesized and thoroughly characterized, with a focus on Eu III and Tb III complexes as visible emitters and Nd III, Er III, and Yb III complexes as infrared emitters. Investigation of the crystal structures of the complexes in powder form and as single crystals by using X‐ray diffraction revealed five different structural types, including monomeric, dimeric, and polymeric. The local structure in different solutions was studied by using X‐ray absorption spectroscopy. The photoluminescence quantum yields (PLQYs) of terbium and europium complexes were 39 and 15 %, respectively; the latter value was increased almost twice by using the heterometallic complex [Tb0.5 Eu0.5 (pfb)3 (H2 O)] (Hpfb=pentafluorobenzoic acid). Due to the effectively utilized sensitization strategy (pfb) − →Tb→Eu, a pure europium luminescence with a PLQY of 29 % was achieved. Abstract : Luminescent lanthanides : A series of highly luminescent, photostable, and soluble lanthanide pentafluorobenzoates have been synthesized and characterized, with a special focus on Eu III and Tb III complexes as visible emitters and Nd III, Er III, and Yb III complexes as IR emitters (see figure). Powder and single‐crystal X‐ray diffraction data showed five different structural types, including monomeric, dimeric, and polymeric.